Implementation of Deelneming in Tax Criminal Actions - Nur Ariatmoko (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This research explores tax crimes within the framework of the Law on general regulations and tax procedures (UUKUP), focusing on mandatory contributions to the state by individuals and entities. Utilizing normative methodologies, including statutory analysis, conceptual exploration, and case studies, the study scrutinizes participation in tax crimes. Statutory analysis examines existing laws to identify gaps in the legal framework, while conceptual exploration establishes a theoretical foundation for understanding criminal actions and participation in taxation. Case studies analyze real-world instances, extracting insights. The findings reveal a gap in regulating the capacity and role of tax crime perpetrators. This gap is evident in the application of laws, lacking explicit regulations on criminal actions and participation, weakening implementation. Determining involvement is discretionary, hindering effective enforcement. This study emphasizes the need for comprehensive legislation on taxation-related criminal acts, defining participation parameters. Strengthening the legal framework enhances efficacy in combating tax crimes, providing a robust foundation for judicial decisions and equitable enforcement